2006
DOI: 10.1002/14651858.cd004535.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Stavudine, lamivudine and nevirapine combination therapy for treatment of HIV infection and AIDS in adults.

Abstract: The combination of nevirapine, 3TC and d4T is as efficacious as a combination of efavirenz, 3TC and d4T. Once-daily NVP with twice-daily 3TC and d4T is as efficacious as twice-daily NVP, 3TC and d4T. However, toxicity may be increased in the once-daily NVP regime. Additional trials of sufficient duration are required to provide better evidence for the use of this combination as a first line therapy. Ideally, trials should use standardised assessment measures especially with respect to measuring viral load, so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
4
19
0
Order By: Relevance
“…247−259 We identified and appraised longitudinal studies of antiretroviral treatment, 260,261 a meta-analysis on behaviour change related to HIV screening tests, 249 a meta-analysis on antiretroviral therapy 256 and a Cochrane systematic review on antiretroviral treatment. 247 One hundred and four titles addressed the burden of HIV and barriers to care for immigrant populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…247−259 We identified and appraised longitudinal studies of antiretroviral treatment, 260,261 a meta-analysis on behaviour change related to HIV screening tests, 249 a meta-analysis on antiretroviral therapy 256 and a Cochrane systematic review on antiretroviral treatment. 247 One hundred and four titles addressed the burden of HIV and barriers to care for immigrant populations.…”
Section: Resultsmentioning
confidence: 99%
“…In another meta-analysis, Siegfried and coauthors 247 reported a relative risk of 1.3 for adverse events associated with antiretroviral treatment. However, most adverse events, including metabolic disturbances associated with cardiovascular events, can be ameliorated by changes in regimen or appropriate treatment.…”
Section: Screening Testsmentioning
confidence: 99%
“…Finally, in their recent Cochrane revision of April 2006 (17), Siegfried et al assessed nevirapinebased regimens as providing favorable efficacy and durability, associated with a contained adverse effect profile and potential for drug-drug interactions. In the published series quoted above (1,17), around 40% of treated patients were represented by females, and no significant difference as to toxicity and efficacy was found compared with efavirenz-treated subjects (17).…”
Section: Resultsmentioning
confidence: 89%
“…This last FDA statement does not seem well substantiated, since the large majority of studies were conducted on pregnant women (5-7) (while the advisory included all women, regardless of pregnancy) (14), and it was stated that single-dose nevirapine was less toxic than b.i.d. administration, while the large 2NN study demonstrated a slight increased toxicity just for once-daily nevirapine administration (19), other non-comparative surveys failed in retrieving reduced hepatotoxicity with once-daily nevirapine (1), a very recent Cochrane review (17) underlined a possible increased toxicity when nevirapine is delivered once daily (17), and also pharmacokinetic studies disclosed greater Cmin/Cmax nevirapine values when this drug is administered once daily (8). Later, a large retrospective study published in the year 2006 and regarding 197 pregnant women exposed to nevirapine for at least 7 days, disclosed a 5.6% overall rate of toxicity, no fatalities, and especially no serious hepatotoxicity save one case of grade-4 cholestasis (possibly attributable to underlying conditions) (6).…”
Section: S H O R T C C O M M U N I C At I O N S / N O T Ementioning
confidence: 99%
“…Since its introduction to the market in 1994, stavudine has been widely used in combination antiretroviral therapy for the treatment of HIV infections in adults and children (Lea and Faulds, 1996;Siegfried et al, 2006). The mechanism of action of stavudine involves sequential phosphorylation by cellular kinases to its active metabolite, stavudine-5Ј-triphosphate, which inhibits the HIV-1 reverse transcriptase enzyme, and causes DNA chain termination by incorporating into viral DNA (Huang et al, 1992).…”
mentioning
confidence: 99%